Curriculum as Renewal - Krasny, Karen; Brushwood Rose, Chloë (Journal of the Canadian Association for Curriculum Studies, 2023)
Journal for the Canadian Association for Curriculum Studies Editorial for Volume 7 Number 2 2009.